PENGEMBANGAN MODUL IPA BERBASIS ISLAMIC SCIENCE TECHNOLOGY ENGINEERING AND MATHEMATICS PADA MATERI HUKUM NEWTON - Misbahul Jannah; Wati Oviana; Iin Nurhalizha (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
AbstractThe problem it is found that at the university there is no (Islamic Science, Technology, Engineering, and Mathematics) I-STEM learning module as a guide for lecturers in implementing science learning. For this reason, this study aims to (1) Design Islamic STEM-based science modules on Newton's Law material (2) Assess Islamic STEM-based science modules on Newton's Law material. This study uses a Design Development Research (DDR) approach using the Dick and Carey instructional design model. The sample of this research is three experts, three senior lecturers and six science lecturers. The instruments of this research are observation sheets, interviews and questionnaires which are analyzed using qualitative and quantitative analysis. Qualitative analysis is used for need analysis and module design. While the quantitative analysis for the assessment of the module which is analyzed using SPSS and excel. The results showed that (1) Islamic STEM-based science module design in Newton's Law material followed the three steps of the Dick and Carey instructional design model, namely needs analysis, module development and module assessment. (2) The results of assessment by expert, senior lecturers and science lecturers show that Islamic STEM-based science modules on Newton's law material are appropriate for using in the science learning process in universities.AbstrakPermasalahan di lapangan didapati bahwa di universitas belum tersedianya modul pembelajaran berbasis Islamic STEM (I-STEM) sebagai panduan bagi dosen dalam melaksanakan pembelajaran IPA. Untuk itu, penelitian ini bertujuan (1) Mendesain modul IPA berbasis I-STEM pada materi Hukum Newton (2) Menilai modul IPA berbasis I-STEM pada materi Hukum Newton. Penelitian ini menggunakan pendekatan Design Development Research (DDR) dengan menggunakan model desain instruksional Dick and Carey. Sampel penelitian ini adalah tiga orang pakar, tiga orang dosen senior dan enam orang dosen IPA. Adapun instrumen penelitian ini adalah lembar observasi, wawancara dan angket yang dianalisis menggunakan analisis kualitatif dan kuantitatif. Analisis kulaitatif digunakan untuk analisis kebutuhan dan dan desain modul. Sedangkan analisis kuantitatif untuk penilaian modul yang dianalisis dengan menggunakan SPSS dan excell. Hasil Penelitian menunjukkan (1) Desain modul IPA berbasis I-STEM pada materi Hukum Newton mengikut tiga langkah dari model desain instruksional Dick and Carey yaitu analisis kebutuhan, pengembangan modul dan penilaian modul. (2) Hasil penilaian pakar, dosen senior dan dosen IPA menunjukkan bahwa modul IPA berbasis I-STEM pada materi hukum Newton layak digunakan dalam proses pembelajaran IPA di perguruan tinggi.